The PENGEMBANGAN E-BOOK BERBASIS 3D PAGEFLIP PRO PADA MATERI EKOSISTEM UNTUK SISWA KELAS VII SMPN PONTIANAK - Afandi Afandi; Andi Besse Tenriawaru; Alfeus Ardiansa Manurung (Akademika, 2022)
This study was structured with the aim of knowing the feasibility of student learning media at SMPN 16 Pontianak, SMPN 11 Pontianak, and SMPN 6 Pontianak on ecosystem materials, knowing the process of developing media. e-book based on 3D Pageflip Pro, and knowing the validity and reliability of the developed learning media. The research method used is Research and Development with a model Four-D. In this research, it is reduced to a development model Three-D includes stages define (definition), design (design), and develop (development) to step expert appraisal (expert judgment). The data sources for this study were 60 seventh-grade students from SMPN 16 Pontianak, SMPN 11 Pontianak, and SMPN 6 Pontianak, as well as 3 biology science teachers from each of these schools and 2 lecturers of Biology Education FKIP Untan. The result of the validity of the 3D Pageflip Pro-based ebook media is v 0.80 valid category. The results of inter-rater reliability using the ICC get results from 0.5 to 0.851 in the good category. 3D Pageflip Pro-based e-book media that has met the good criteria and deserves to be declared for use